PENGARUH KEPUASAN KERJA, KEADILAN ORGANISASIONAL DAN PEMBERDAYAAN KARYAWAN TERHADAP KOMITMEN ORGANISASIONAL KARYAWAN - Saputra, I Made Angga; Wibawa, I Made Artha (E-Jurnal Manajemen; Vol 7 No 6 (2018), 2018)
Organizational commitment is the extent to which a person identifies himself with the organization and his willingness to maintain membership through the loyal attitude that employees have toward the organization. Employee commitment to the organization becomes a matter of note because it will have an impact on the achievement of organizational goals. The purpose of this study was to determine the effect of job satisfaction, organizational justice and employee's loyalty to organizational commitment. Sampling in this study using proportional random sampling technique, using 60 respondents. The data were collected by distributing questionnaires using a 5-point Likert scale to measure 42 item statements. The analysis technique used is Multiple Linear Regression Analysis. Based on the results of the analysis found that the variable of job satisfaction, organizational justice and empowerment of employees have a positive and significant impact on organizational organizers at Amanusa Hotel Nusa Dua employees. These results indicate that the higher the level of job satisfaction, organizational justice and employee empowerment perceived employee, the higher commitment of employees to the organization. Parties should always pay attention to job satisfaction, organizational justice and empowering employees by providing opportunities to increase salaries and empower employees so that employees will have a high commitment to the organization